Geekie, J. y Read, J. (2012). El sentido de la locura. Barcelona: Herder. - Valiente, Rosa M. (Revista de Psicopatología y Psicología Clínica, 2014)
Geekie, J. y Read, J. (2012). El sentido de la locura. Barcelona: Herder. 350 pp.